Selective separation of chalcopyrite from sphalerite with a novel depressant fenugreek gum: Flotation and adsorption mechanism. (30th June 2022) - Wang, Changtao; Liu, Runqing; Wu, Meirong; Zhai, Qilin; Luo, Yuanjia; Jing, Nianwen; Xie, Feifei; Sun, Wei
Highlights: Sphalerite was selectively depressed using FG as depressant in chalcopyrite flotation. FG chemisorbed on sphalerite through COH and OCO groups. Zn sites on sphalerite crystal supported FG chemical chelation. The adsorbed FG could be replaced by EX on chalcopyrite surface. Abstract: Selective separation of chalcopyrite from sphalerite is a challenge in mineral processing. This study is the first to use the organic compounds in fenugreek gum (FG) as a depressant for sphalerite to aid this separation. The results showed that FG exerts a selectively inhibiting effect on sphalerite in chalcopyrite flotation and thus is a potential sphalerite depressant. The underlying mechanisms were studied by contact-angle measurements, atomic force microscopy (AFM) imaging, Fourier transform infrared (FTIR) spectroscopy, and X-ray photoelectron spectroscopy (XPS). Overall, FG showed weak adhesion to the chalcopyrite surface and was easily replaced by ethyl xanthate through competitive adsorption. In addition, FG showed greater adsorption capacity for sphalerite and was more stable. According to the detailed mechanism, the Cu and Fe sites on chalcopyrite did not adsorb FG effectively, and the Zn sites on sphalerite were much more active and aided chemical chelation with the C-OH and O-C-O groups of FG. Herein, selective separation of chalcopyrite from sphalerite was achieved using FG as an effective depressant.